2002
DOI: 10.1089/152702902753639540
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Polycythemia-Induced Increase in Arterial Oxygen Content to Suppress the Anorexic Effect of Simulated High Altitude in the Adult Rat

Abstract: The anorexic effect of exposure to high altitude may be related to the reduction in the arterial oxygen content (Ca(O2)) induced by hypoxemia and possibly the associated decreased convective oxygen transport (COT). This study was then performed to evaluate the effects of either transfusion-induced polycythemia or previous acclimation to hypobaria with endogenously induced polycythemia on the anorexic effect of simulated high altitude (SHA) in adult female rats. Food consumption, expressed in g/d/100 g body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Other workers also reported lower levels of circulating leptin on HA exposure. Norese et al (2002) have reported decreased leptin levels in mice exposed to simulated altitude of 4560 m and conclude that at least in case of rodents leptin is probably not causally implicated in the energy imbalance observed at HA. Lower levels of circulating leptin were observed in HA natives as compared to sea level residents (Woolcott et al 2002;Cabrera de Leon et al 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Other workers also reported lower levels of circulating leptin on HA exposure. Norese et al (2002) have reported decreased leptin levels in mice exposed to simulated altitude of 4560 m and conclude that at least in case of rodents leptin is probably not causally implicated in the energy imbalance observed at HA. Lower levels of circulating leptin were observed in HA natives as compared to sea level residents (Woolcott et al 2002;Cabrera de Leon et al 2004).…”
Section: Discussionmentioning
confidence: 97%
“…However, studies on rodents exposed to simulated altitude have shown decreased leptin levels (Raff et al 1999, Norese et al 2002. Yasumasu et al (2002) have reported about 50% decreased leptin secretion in case of in vitro cultured adipocytes exposed to low oxygen concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Tschöp et al (1998) reported elevated serum leptin levels in human subjects at high altitude, and this was considered the mechanism of high altitude anorexia. However, results of subsequent studies on animal models and natives of different altitude appear to be contradictory (Norese et al, 2002;Woolcott et al, 2002).…”
Section: Luanne Freermentioning
confidence: 99%
“…In our study it was difficult to isolate the effect of cold and hypoxia, though the subjects were provided adequate protecting clothing. Norese et al (2002) have reported decreased leptin levels in female mice exposed to simulated high altitude (5460 m) with controlled temperature, and on the basis of their studies and other animal studies on rats, they concluded that, at least in case of rodents, leptin is not a player in altered energy homeostasis at high altitude that leads to anorexia and loss of body mass. Woolcott et al (2002) found a lower level of serum leptin in high altitude natives in comparison to sea-level residents.…”
Section: Luanne Freermentioning
confidence: 99%